2019
DOI: 10.1111/avj.12896
|View full text |Cite
|
Sign up to set email alerts
|

Breed is associated with the ABCB1‐1Δ mutation in Australian dogs

Abstract: Objective The ABCB1 gene encodes P‐glycoprotein (P‐gp), a cellular membrane pump. One functional mutation that leads to expression of a less functional form of P‐gp, ABCB1‐1Δ, has been described in dogs. Individuals with this mutation can have severe adverse reactions to common veterinary pharmaceuticals that are known substrates of this pump. We investigated the detection of this mutation in samples submitted to two Australian diagnostic laboratories. Methods A total of 4842 dogs across 27 breeds were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A polymorphism in the ABCB1 gene affects intact HPA axis response in depressed human patients Individuals who lack ABCB1, as it occurs in some breeds of dogs with the ABCB1-1 mutation (45), have severe adverse reactions to common medications that act as substrates of this transporter, such as immunosuppressants and steroid hormones (46). Previous studies have shown that dogs and rodents lacking a functional Abcb1/ ABCB1 gene have a blunted HPA axis response compared to wild-type animals (41,47).…”
Section: Abcb1 Is Overexpressed In Adrenocortical Samples From Patien...mentioning
confidence: 99%
“…A polymorphism in the ABCB1 gene affects intact HPA axis response in depressed human patients Individuals who lack ABCB1, as it occurs in some breeds of dogs with the ABCB1-1 mutation (45), have severe adverse reactions to common medications that act as substrates of this transporter, such as immunosuppressants and steroid hormones (46). Previous studies have shown that dogs and rodents lacking a functional Abcb1/ ABCB1 gene have a blunted HPA axis response compared to wild-type animals (41,47).…”
Section: Abcb1 Is Overexpressed In Adrenocortical Samples From Patien...mentioning
confidence: 99%
“…While reported first in the collie, multidrug sensitivity caused by the ABCB1-1Δ variant has been described in a wide variety of dog breeds: collies and collie-like dogs but also seemingly unrelated breeds [ 15 , 19 , 20 , 26 ] and cross-bred dogs [ 21 , 22 ]. Interestingly, the presence of this variant could be traced back to the collie lineage for the longhaired whippet, silken windhound [ 15 ], and white Swiss shepherd dog [ 18 ], who all share the ABCB1-1Δ variant identical by descent (IBD) with herding breeds from the collie lineage.…”
Section: Discussionmentioning
confidence: 99%
“…This link to a white coat and the fact that the white Swiss shepherd (for which IBD was established [ 18 ]) originated from the white German shepherd dog indicates the variant has the same origin as all other breeds [ 24 ]. However, to the authors’ knowledge, there is no known IBD link between the collie lineage and the cocker spaniel, labradoodle, and several crossbreeds in which the ABCB1-1Δ variant has also been reported [ 20 22 ]. Furthermore, independent laboratories have reported the presence of the variant in more breeds seemingly unrelated to collies, like the black mouth cur, Carolina dog, and chinook [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations